Lexical Collocations in English Teaching Modules: An In-depth Analysis - Muttaqin, Dedy Ahsan (LPPM Universitas Bumigora Mataram, 2024)
This research aimed to investigate lexical collocation in English teaching modules. The method of this study was designed as quantitative research. This research was a corpus-based study. The data was collected from an online platform, Platform Merdeka Mengajar (PMM). This study attempted to find answers to the research questions: What are lexical collocations in EFL classrooms? What are the frequencies of lexical collation in EFL classrooms? The researcher was equipped with AntCont to generate a wordlist and frequency and with COHA to do an analysis. The findings show that English teachers lack lexical collocation frequency in their teaching modules. The researcher found that the highest category of verbs and nouns dominated the corpus. The recommendation for EFL teachers is essential to expose lexical collocation in their teaching modules and to contribute to the knowledge mastery of lexical collocation and its application in the classroom context.